Aliens, clowns & geeks [videorecording (DVD)] - Elfman, Richard; Elfman, Richard; Elfman, Bohdi, 1969-; Forsythe, Rebecca; Agee, Steve, 1969- (Elfmaniac Media, 2022)
When an out-of-work actor discovers a key to the universe, he becomes drawn into a battle between killer clowns and aliens and must find a way to save the world from the evil invaders.